The Silence of the Mind: Intellectual Stagnation and the Unmaking of an Empire - Hasbi Yusron; Kurniawan Maspul (Pubmedia Social Sciences and Humanities, 2025)
This paper posits that the Ottoman Empire’s decline was fundamentally rooted in a profound intellectual crisis, a deeper malady beneath its political and military failures. Employing an Ibn Khaldun-inspired civilisational lens, we argue that the empire entered a terminal phase marked by epistemological, institutional, and applied stagnation. The analysis traces this trajectory through poignant symbols: the state-sponsored destruction of the Istanbul Observatory in 1580, which extinguished empirical research; the deliberate delay in adopting the printing press due to religious and guild resistance; and a vast knowledge gap evidenced by a 1:38 library volume ratio with France. This intellectual closure crippled adaptive capacity, transforming a once-dynamic culture of integrated learning into a system of rote repetition and doctrinal rigidity. The empire’s eventual collapse serves as a stark historical lesson on the non-negotiable role of a living, questioning intellectual tradition for state survival, with urgent implications for modern nations struggling to build resilient knowledge ecosystems.